2016
DOI: 10.1371/journal.pone.0153681
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Expression Data Identify DCC as a Candidate Gene for Early Meningioma Progression

Abstract: Meningiomas are the most common primary brain tumors bearing in a minority of cases an aggressive phenotype. Although meningiomas are stratified according to their histology and clinical behavior, the underlying molecular genetics predicting aggressiveness are not thoroughly understood. We performed whole transcript expression profiling in 10 grade I and four grade II meningiomas, three of which invaded the brain. Microarray expression analysis identified deleted in colorectal cancer (DCC) as a differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Other underexpressed genes have roles in cell adhesion. For instance, COL8A1 was identified by microarray analysis to be down-regulated in meningiomas, [ 56 , 66 ]. In addition, in our underexpressed gene cohort, GO enrichment analysis (biological process) identifies a number of genes involved in various aspects of regulation of cell adhesion, cell-cell adhesion, and cell- substrate or -matrix adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Other underexpressed genes have roles in cell adhesion. For instance, COL8A1 was identified by microarray analysis to be down-regulated in meningiomas, [ 56 , 66 ]. In addition, in our underexpressed gene cohort, GO enrichment analysis (biological process) identifies a number of genes involved in various aspects of regulation of cell adhesion, cell-cell adhesion, and cell- substrate or -matrix adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Grade I meningiomas are not aggressive but Grade II malignancies are known to infiltrate the surrounding brain tissue. A study that classified these tumors according to the expression of the tumor suppressor gene deleted in colorectal cancer (DCC), whose loss marks the aggressiveness of the meningiomas, showed that the expression of BHLHE40 was significantly upregulated in the DCC low (highly aggressive) tumors [76]. Taken together, these studies demonstrate that in all subtypes of brain carcinoma, tumor aggression is associated with an increase in the expression of BHLHE40.…”
Section: Brain Tumorsmentioning
confidence: 95%
“…Previously, we published gene expression profiles for most of the meningioma patients’ tissues collected for our cohort [ 64 , 65 ], as well as for their corresponding cell lines [ 22 ]. For this work, we aimed to determine the hetero-dynamic characteristics of MCSCs in situ and identify differential patterns associated with grades II/III tumors.…”
Section: Introductionmentioning
confidence: 99%